General Geology and Facies Characteristics of the Lambir Formation, Miri-Lambir, Sarawak, With Special Emphasis on Its Trace Fossil Contents - Bin Saifulbahri, Ezzat Amirimran (Universiti Teknologi PETRONAS, 2016)
Ichnofabric analysis is based on observations in cross-section or exposed outcrop and the approach are frequently emphasises on the synecology of endobenthic community. However, in the exposed Lambir Formation in Pantai Tusan of Miri-Lambir, palaeoichnological study has not been extensively done compared to sedimentological facies and facies associations study. Five sedimentary facies has been identified, which are trough cross bedded sandstone facies, cross laminated sandstone facies, thoroughly laminated sandstone facies, thin laminated mudstone and sandstone facies, and bioturbated mudstone. Ichnofossils also has been identified as these facies. Those ichnofossils are Arenicolites, Bichordites, Cylindrichnus, Ophiomorpha, Palaeophycus, Planolites, Rosselia, Skolithos, Teichichnus, Thalassinoides, ?Sinusichnus, Taphrhelminthopsis, ?Trichichnus, and cf. Zoophycos. From facies and ichnofossils that has been observed, two facies associations; tidal sand bar facies association and tidal flat facies association; and two ichnofacies; Skolithos ichnofacies and Cruziana ichnofacies; has been identified. Based on the integrated studies, the sedimentary succession were deposited in tide-dominated estuary environment.